1998
DOI: 10.1038/bjc.1998.159
|View full text |Cite
|
Sign up to set email alerts
|

The photodynamic response of two rodent tumour models to four zinc (II)-substituted phthalocyanines

Abstract: Summary Four novel zinc (I1)-substituted phthalocyanines, varying in charge and hydrophobicity, were evaluated in vivo as new photosensitizers for photodynamic therapy. Two rat tumours with differing vascularity were used: a mammary carcinoma (LMC,) and a fibrosarcoma (LSBD1), with vascular components six times higher in the latter (10.8% ± 1.5) than in the former (1.8% ± 1.4). Each sensitizer was assessed for tumour response relative to normal tissue damage, and optimum doses were selected for further study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…The pattern of tumour growth delay over the time course was similar for both a 652 nm diode laser ( Figure 3) and a 652 nm Copper Vapour pumped dye laser (data not shown) with no significant difference between the two sources. After most treatments, there was an immediate increase in tumour diameter that regressed after approximately 24 h. This oedema is a shortlived inflammatory response due more to the insertion of the fibre than PDT and has also been observed with other photosensitisers in this model (Cruse-Sawyer et al, 1998).…”
Section: Photodynamic Therapy Efficacy Of M-thpc In the Bdix Ratsupporting
confidence: 69%
“…The pattern of tumour growth delay over the time course was similar for both a 652 nm diode laser ( Figure 3) and a 652 nm Copper Vapour pumped dye laser (data not shown) with no significant difference between the two sources. After most treatments, there was an immediate increase in tumour diameter that regressed after approximately 24 h. This oedema is a shortlived inflammatory response due more to the insertion of the fibre than PDT and has also been observed with other photosensitisers in this model (Cruse-Sawyer et al, 1998).…”
Section: Photodynamic Therapy Efficacy Of M-thpc In the Bdix Ratsupporting
confidence: 69%
“…To date there have been few studies of neutral photosensitizers, in part because of problems with water-solubility. Similar results were found for comparison of the same or similar sensitizers in a transplanted fibrosarcoma in the rat (Cruse-Sawyer et al, 1998). Both this study and the recent study referred to above (Cruse-Sawyer et al, 1998) have suggested that the cationic phthalocyanine is the most effective in PDT.…”
Section: Effects Of Charge On Pdt Efficacysupporting
confidence: 77%
“…Similar results were found for comparison of the same or similar sensitizers in a transplanted fibrosarcoma in the rat (Cruse-Sawyer et al, 1998). Both this study and the recent study referred to above (Cruse-Sawyer et al, 1998) have suggested that the cationic phthalocyanine is the most effective in PDT. It was not possible to determine octanol:water partition coefficients because, for each sensitizer, almost all of the sensitizer was found in the aqueous layer.…”
Section: Effects Of Charge On Pdt Efficacysupporting
confidence: 77%
See 1 more Smart Citation
“…The response of cells to photodynamic therapy (PDT) † appears to depend on a number of factors, one of which is the ¶Posted on the website on 22 sensitizer used. Following the development of Photofrin , numerous so-called second generation sensitizers have been developed which have shown good activity in vitro and in vivo (1)(2)(3). Charge and hydrophobicity appear to be the main factors governing cellular localization (1), with localization being the major determinant of cell death (2,4).…”
Section: Introductionmentioning
confidence: 99%